Predicting psychosocial risk in pediatric kidney transplantation: An exploratory cluster analysis of a revised Pediatric Transplant Rating Instrument. (14th December 2022) - West, Kara B.; Plevinsky, Jill M.; Amaral, Sandra; Laskin, Benjamin; Lefkowitz, Debra S.
Abstract: Background: The Pediatric Transplant Rating Instrument (P‐TRI) is a 17‐item scale developed to assess psychosocial risk factors for poor outcomes after solid organ transplantation. Research has identified the limitations of the original instrument and proposed revisions to improve clinical utility. This project examined patterns of risk in children being evaluated for kidney transplant using a revised P‐TRI. Methods: A multidisciplinary kidney transplant team revised the P‐TRI. A social worker and a psychologist collaboratively completed the modified instrument for 37 children after the psychosocial pretransplant evaluation. Electronic medical records were reviewed for transplant status (transplanted, active waitlist, inactive) 1 year later. Exploratory cluster analyses and chi‐square tests examined patterns of risk and correlates with cluster membership. Results: Three clusters were identified. The high‐risk group (29.7%) had difficulties with medication and appointment adherence, strained relationships with the medical team, and the presence of parent psychiatric history. The medium‐risk group (35.1%) had difficulties with parent knowledge, financial strain, and risk factors for medication nonadherence. The low‐risk group (35.1%) demonstrated no difficulties with adherence or financial strain. Clusters were prospectively associated with transplant status, such that those in the high‐risk group were less likely to be transplanted within 1 year post‐evaluation. Conclusions: The revised P‐TRI demonstrated good construct validity as risk level appeared to be associated with transplant listing status 1 year post‐evaluation. These results suggest that standardized pretransplant psychosocial risk assessment tools may have value in optimizing transplant access if they can be paired with targeted, multidisciplinary interventions to address concerns early in the transplant process.